Compression bioreactor-based mechanical loading induces mobilization of Human bone Marrow-Derived Mesenchymal stromal cells into collagen scaffolds in vitro - Gamez, Carolina; Schneider-Wald, Barbara Katharina; Bieback, Karen; Schütte, Andy; Büttner, Sylvia; Hafner, Mathias; Gretz, Norbert; Schwarz, Markus (International journal of molecular sciences, 2020)
Articular cartilage (AC) is an avascular tissue composed of scattered chondrocytes embedded in a dense extracellular matrix, in which nourishment takes place via the synovial fluid at the surface. AC has a limited intrinsic healing capacity, and thus mainly surgical techniques have been used to relieve pain and improve function. Approaches to promote regeneration remain challenging. The microfracture (MF) approach targets the bone marrow (BM) as a source of factors and progenitor cells to heal chondral defects in situ by opening small holes in the subchondral bone. However, the original function of AC is not obtained yet. We hypothesize that mechanical stimulation can mobilize mesenchymal stromal cells (MSCs) from BM reservoirs upon MF of the subchondral bone. Thus, the aim of this study was to compare the counts of mobilized human BM-MSCs (hBM-MSCs) in alginate-laminin (alginate-Ln) or collagen-I (col-I) scaffolds upon intermittent mechanical loading. The mechanical set up within an established bioreactor consisted of 10% strain, 0.3 Hz, breaks of 10 s every 180 cycles for 24 h. Contrary to previous findings using porcine MSCs, no significant cell count was found for hBM-MSCs into alginate-Ln scaffolds upon mechanical stimulation (8 ± 5 viable cells/mm3 for loaded and 4 ± 2 viable cells/mm3 for unloaded alginate-Ln scaffolds). However, intermittent mechanical stimulation induced the mobilization of hBM-MSCs into col-I scaffolds 10-fold compared to the unloaded col-I controls (245 ± 42 viable cells/mm3 vs. 22 ± 6 viable cells/mm3, respectively; p-value < 0.0001). Cells that mobilized into the scaffolds by mechanical loading did not show morphological changes. This study confirmed that hBM-MSCs can be mobilized in vitro from a reservoir toward col-I but not alginate-Ln scaffolds upon intermittent mechanical loading, against gravity.